Pengaruh Financial Ratio dan Profit Growth Dimasa Pandemi Covid-19 - Median Wilestari; Rika Arpiani (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2023)
The purpose of this study is to determine the profit growth of companies in the consumer goods industry sector which are listed on the Indonesia Stock Exchange. Judging from the financial ratios, liquidity ratios, solvency ratios, activity ratios and profitability ratios. The population of this study is the consumer goods industry sector which has obtained annual financial reports (annually reports) published on the Indonesia Stock Exchange for the 2018-2021 period. The data collection technique used in this study was purposive sampling, namely the method of selecting samples on previously known characteristics so that 13 samples were obtained. The analysis technique used in this research is descriptive analysis with multiple linear regression analysis method, classic assumption test, independent simple T-Test different test with SPSS 25 program. The results showed that, (1) the current ratio has no significant positive effect on the growth variable profit, (2) debt ratio has a significant positive effect on profit growth variable, (3) total asset turnover has no significant negative effect on variable, (4) net profit margin has significant positive effect on profit growth variable.